Pengaruh Label Halal, Harga Dan Citra Merek Terhadap Minat Beli Konsumen Kosmetik Skincare Melalui Aplikasi Tiktok Pada Masyarakat Di Kota Mataram - Amaliah, Dina; yusuf, Mohammad; Zulpawati, Zulpawati (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
The purpose of the study is to examine the effects of halal labeling, price, and brand image on the purchasing intention of cosmetic or skincare consumers through Tiktok Application among the population of Mataram City. The study utilized a random sampling technique, and the sample size consisted of 100 respondents. It is a quantitative study that employs primary data. The data collection technique used in the study is a questionnaire, and the data analysis tool used is SPSS version 25.0. The quality of the data is tested using validity and reliability tests. The analytical technique used in the study is multiple linear regression, and the study employs partial correlation, simultaneous testing, and determination coefficient testing. Based on the data analysis, the results obtained from the t indicate that the partial effects of halal labeling and brand image significantly influence consumer purchasing intention of cosmetics among the residents of Mataram City. Each independent variable (halal labeling, brand image) has a t-value exceeding the t-table, while the price variable shows insignificant influence as its t-value is less than the t-table. From the F-test, it can be explained that halal labeling, price, and brand image simultaneously have a significant effect on consumer purchasing intention of cosmetics or skincare through TikTok application among the residents of Mataram City. The obtained F-value of 12.642 is greater than the F-table value of 2.72. The coefficient of determination analysis indicates that halal labeling, price, and brand image affect consumer purchasing intention of cosmetics/skincare through TikTok application among the residents of Mataram City by 28.3%, while the remaining 71.7% is influenced by other variables outside of this research model